L'ouverture d'un apprentissage musical global dans l'institution scolaire. Les Écoles secondaires de musique en Grèce - Reguina Hatzipetrou-Andronikou
From the 1980s onwards, the music education landscape in Greece has been transformed by the creation of secondary music schools. Integrating multiple hours of music lessons into the high school curriculum, they train students simultaneously in classical and traditional music, in both theory and practice. This paper shows how this unprecedented schooling of music, although still fragile, contributes to transforming music education. The introduction of traditional music destabilizes the symbolic monopoly of classical music, especially since it is accompanied by the introduction of informal learning practices and thus breaking with conservatories' long-established formal learning methods. Nevertheless, the "normalisation" of traditional music within music education remains uncertain, especially since the new teaching category providing this education, the teachers of music subjects, has remained a structurally young and precarious category for the last thirty years.